Identifikasi Keanekaragaman Spesies Elasmobranchii Hasil Tangkapan Nelayan Lokal Yang Didaratkan di Taman Wisata Perairan Timur Pulau Bintan - Zamalludin, Zamalludin; Karlina, Ita; Hikmat Nugraha, Aditya; Armanto, Tri; Yandri, Fahmi; Angraini, Rika; Koenawan, Chandra Joei (JURNAL ENGGANO, 2024)
Riau Islands Province has a larger water area than its land. This large water area then began to be managed with the establishment of a conservation area known as the Bintan Island Eastern Waters Tourism Park. The vast waters in the Riau Islands are thought to also have high diversity, one of which is Elasmobranchii species. The purpose of this study is to identify the species diversity and conservation status of Elasmobranchii from the catches landed by local fishermen in Bintan Island Eastern Waters Tourism Park. The method used in this study is a survey method, which is descriptive to determine the description of the results of the identification of species diversity and conservation status of Elasmobranchii. From the results of this study, 12 species and 8 families of 72 Elasmobranchii individuals were identified, with a diversity index value of H' = 2.21 (medium), uniformity index E = 0.89 (very good), and dominance index C = 0.14 (low) or no dominating species. From the conservation status analysis, it was found that 42% or 5 out of 12 Elasmobranchii species were categorized as Vulnerebel, 25% (3 species) were categorized as endangered and 8% (1 species) were categorized as critically endangered, 75% of Elasmobranchii species landed at the study site had a decreasing population status.   Keywords: Bintan, Elasmobranchii, Diversity, Conservation